PARTISIPASI MASYARAKAT DALAM PENYUSUNAN ANGGARAN PENDAPATAN BELANJA DESA (APBDes) TAHUN ANGGARAN 2012/2013 DI DESA SUMERTA KAJA, KECAMATAN DENPASAR TIMUR - Adi Artana, I Made; Erviantono, S.IP, M.Si, Tedi; Purnamaningsih, SH., M.AP, Putu Eka (CITIZEN CHARTER, 2015)
ABSTRACT Participation is one of Good Governance characteristic and such a good attitude of the governance. One type of people participation is arranging Anggaran Pendapatan dan Belanja Desa (APBDes). As same as like people of Sumerta Kaja village at Kecamatan Denpasar Timur, have their whole power to manage their consideration that village goverment given to them. With that condition, the main purpose of this study is to know how far is people participation on making Anggran Pendapatan dan Belanja Desa (APBDes) who done by the village government of Sumerta Kaja Kecamatan Denpasar Timur. The people’s participation will proof the people consideration of improving the participation to build the village together and also people of Sumerta Kaja know the program which implemented by their government by the arranging the APBDes. This study used qualitative descriptive method, to get the data; researcher observed by himself the phenomenon in the field and interviewed the people that have correlation with this partnership of making APBDes. The conclusions that got on this study are first the people participation is just on planning and suggestion, second their participation is totally seen when building character of village consideration where the consideration that they receive is totally their whole power to manage it. Keyword: Participation, APBDes, Public Policy